CERVICAL EROSION - Najmiddinova Nazira Pardaboyevna; Obloqulova Iroda Amriddin qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Abstract: This article is intended to describe the causes of uterine erosion, its clinical treatment, the use of modern methods of treatment in this disease, and the use of modern techniques.